2-Methoxyestradiol combined with ascorbic acid facilitates the apoptosis of chronic myeloid leukemia cells via the microRNA-223/Fms-like tyrosine kinase 3/phosphatidylinositol-3 kinase/protein kinase B axis. Issue 2 (1st February 2022) - Zhang, Suwei; Yu, Hanhui; Li, Jiazhen; Fan, Jingru; Chen, Jingchao
ABSTRACT: Chronic myeloid leukemia (CML) is a malignant myeloproliferative tumor. 2-Methoxyestradiol (2-ME) is an endogenous estrogen metabolite that shows efficacy in human malignancies. Ascorbic acid (AA) possesses antioxidant activity. This study explored the mechanism of 2-ME combined with AA in the apoptosis of CML cells. Firstly, human CML cell lines were treated with 2-ME and AA. The cell viability, apoptosis, reactive oxygen species (ROS), and mitochondrial membrane potential (MMP) were detected. miR-223 expression in CML cells was detected. In addition, CML cells were transfected with miR-223 inhibitor. The binding relationship between miR-223 and FLT3 was verified. Subsequently, the FLT3 was overexpressed or silenced for the function rescue experiment to confirm the role of FLT3 in CML cell apoptosis. The expression levels of key factors of the PI3K/AKT pathway were detected. Finally, xenograft nude mouse models were established for in vivo verification. 2-ME + AA treatment inhibited CML cell viability and promoted apoptosis, elevated ROS content, and reduced MMP. 2-ME + AA treatment promoted miR-223 expression in CML cells. miR-223 targeted FLT3. Moreover, miR-223 inhibitor or FLT3 overexpression partially annulled the effect of 2-ME + AA on CML cells. 2-ME + AA inhibited the PI3K/AKT pathway via the miR-223/FLT3 axis. Furthermore, 2-ME + AA suppressed CML xenograft growth in mice. Collectively, 2-ME + AA promoted miR-223 expression and suppressed FLT3 and the PI3K/AKT pathway, thereby facilitating the apoptosis of CML cells and inhibiting CML xenograft growth in mice. Graphical abstract: uf0001